1995
DOI: 10.1161/01.cir.91.2.411
|View full text |Cite
|
Sign up to set email alerts
|

Extended Inhibition of Platelet Aggregation With the Orally Active Platelet Inhibitor SC-54684A

Abstract: The results of the dose-ranging study show that oral administration of SCp results in dose-dependent inhibition of platelet aggregation. As shown in the 14-day administration, this dose-dependent inhibition can be maintained for an extended period while exhibiting no adverse effects. SCp is a leading candidate for development and is currently in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

1995
1995
2000
2000

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 16 publications
0
16
0
2
Order By: Relevance
“…These strategies will probably widen the indications for long term platelet inhibition. Results achieved with the intravenously administered monoclonal antibody abciximab, have demonstrated that the efficacy of lIb/IlIa antagonists is additive to that of aspirinJ15] Oral lIb/III antagonists have already been shown to induce dose-dependent inhibition of platelet aggregation for an extended period of time [53] and are currently in clinical development. Long term treatment with these compounds might be beneficial in indications which aspirin lacks efficacy, such as in the prevention of late thrombotic events and/or restenosis following coronary angioplasty.…”
Section: Resultsmentioning
confidence: 99%
“…These strategies will probably widen the indications for long term platelet inhibition. Results achieved with the intravenously administered monoclonal antibody abciximab, have demonstrated that the efficacy of lIb/IlIa antagonists is additive to that of aspirinJ15] Oral lIb/III antagonists have already been shown to induce dose-dependent inhibition of platelet aggregation for an extended period of time [53] and are currently in clinical development. Long term treatment with these compounds might be beneficial in indications which aspirin lacks efficacy, such as in the prevention of late thrombotic events and/or restenosis following coronary angioplasty.…”
Section: Resultsmentioning
confidence: 99%
“…3 A previous study demonstrated that administration of xemilofiban to conscious dogs resulted in dose-dependent antiplatelet activity and a high level of bioavailability. 10 In this report, we assessed for the first time the antithrombotic effectiveness of orally administered xemilofiban or xemilofiban with ASA in a canine model of coronary artery thrombosis. This experimental model allowed us to determine the efficacy of the test agents for prevention of occlusive thrombus formation in response to electrolytic damage of the intimal surface of the LCx.…”
Section: Discussionmentioning
confidence: 99%
“…9 Initial animal studies with xemilofiban demonstrated its effectiveness as an antiplatelet agent. 10 Accordingly, the present investigation determines the antithrombotic activity of orally administered xemilofiban in a canine model of occlusive coro-nary artery thrombosis 9 and tests the hypothesis that targeted levels of inhibition of platelet aggregation by xemilofiban prevent thrombotic occlusion. Moreover, the present experiments determine the antithrombotic effect of a minimally effective dose of xemilofiban combined with oral ASA.…”
mentioning
confidence: 99%
“…The active metabolite SC-54701A is a potent inhibitor of GP IIb/IIIa. 17 A dose-finding study (5 to 20 mg xemilofiban orally bid) after coronary stent deployment in 170 patients, all on aspirin, produced Ͼ50% platelet inhibition at a dose of 10 mg BID. 18 In this small study, no episodes of major bleeding occurred.…”
Section: Eptifibatidementioning
confidence: 99%